Analisis Profil Pemberian Obat Golongan Proton Pump Inhibitor (PPI) pada Penanganan Gastritis - Amalia, Aini; Indriani, Nurul; Kresnapati, I Nyoman Bagus Aji (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2025)
Gastritis is an inflammation of the gastric mucosa that is commonly found in healthcare facilities, including Tripat Regional General Hospital. One of the main therapies for gastritis is the use of Proton Pump Inhibitor (PPI) medications, which work by reducing gastric acid secretion. This study aims to understand the profile of PPI administration in gastritis patients at Tripat Regional General Hospital in 2023. This study uses a retrospective descriptive approach, collecting data from the medical records of outpatient and inpatient patients in 2023. The results show that the number of gastritis cases reached 574 patients. The most commonly used PPI medication is omeprazole (38.4%), with the most frequently prescribed dosage being 20 mg (52.3%), and the most common administration frequency is once a day (93.0%). The conclusion of this study indicates that the use of PPI in gastritis patients at Tripat Regional General Hospital is mostly in accordance with guidelines